Report of the Study Team on Tribal Development Programmes Mysore - Planning Commission (Planning Commission, 1966)
According to the 1961 Census, the tribal population in the Mysore State numbered 1.92 lakhs which is 0.81% of the total population of the State. An estimate made by the Department of Social Welfare puts the present figure at 2,50,000. The Scheduled tribes are found in nearly all the districts with modest concentrations in the districts of Mysore, Coorg and South Kanara.
Committee on Plan Projects, Planning Commission